2022
DOI: 10.3390/cells11050872
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Exercise and Healthspan

Abstract: Healthspan is the period of our life without major debilitating diseases. In the modern world where unhealthy lifestyle choices and chronic diseases taper the healthspan, which lead to an enormous economic burden, finding ways to promote healthspan becomes a pressing goal of the scientific community. Exercise, one of humanity’s most ancient and effective lifestyle interventions, appears to be at the center of the solution since it can both treat and prevent the occurrence of many chronic diseases. Here, we wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 316 publications
(327 reference statements)
0
10
0
Order By: Relevance
“…Both endurance and resistance training reduce myostatin levels. Moreover, the Akt-mammalian target of rapamycin (mTOR) pathway and downstream protein synthesis are particularly stimulated by resistance training such as weight training, whereas the muscle RING-finger protein-1 (MuRF-1) and Atrogin-1 are decreased [ 95 ]. It was demonstrated that patients with long COVID-19 present metabolic alterations such as impairment of fatty acid β-oxidation and increased lactate release during exercise, possibly associated with mitochondrial dysfunctions [ 96 ].…”
Section: Why Physical Activity Could Modulate the Molecular Phenotype...mentioning
confidence: 99%
“…Both endurance and resistance training reduce myostatin levels. Moreover, the Akt-mammalian target of rapamycin (mTOR) pathway and downstream protein synthesis are particularly stimulated by resistance training such as weight training, whereas the muscle RING-finger protein-1 (MuRF-1) and Atrogin-1 are decreased [ 95 ]. It was demonstrated that patients with long COVID-19 present metabolic alterations such as impairment of fatty acid β-oxidation and increased lactate release during exercise, possibly associated with mitochondrial dysfunctions [ 96 ].…”
Section: Why Physical Activity Could Modulate the Molecular Phenotype...mentioning
confidence: 99%
“…Likewise, relative muscle mass ( 31 33 ) and strength ( 34 36 ) are parameters with high predictive power for overall morbidity and mortality. Clearly, the biology underlying maximal endurance and resistance exercise performance confers advantages beyond the athletic arena ( 9 , 37 ), and while differences in physiological capacity between elite athletes and sedentary individuals highlight the huge disparity in performance capacity, they also provide insights into the roles of various organ systems and the potential limits to human performance.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that physical activity can promote health and reduce the risk of cardiovascular disease, cancer, diabetes and other chronic diseases, and there is a strong inverse relationship between physical fitness and mortality in humans [ 1 , 2 ]. However, if the exercise intensity and exercise time exceed a certain limit, the beneficial effect of exercise may be lost, and generate a large amount of ROS through the electron transport chain, which will lead to the oxidation-reduction instability of the body [ 3 ].…”
Section: Introductionmentioning
confidence: 99%